(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the level of health beliefs among students with hearing impairments enrolled in institutions for the hearing impaired, as well as to examine the level of health beliefs according to the variables of gender (male, female). A stratified random sample (equal allocation method) was selected, consisting of 120 male and female students with hearing impairments from government-run institutions for the hearing impaired affiliated with the Ministry of Labor and Social Affairs in Baghdad Governorate. The researchers developed and applied a Health Beliefs Scale after following all necessary scientific steps and procedures. The final version of the scale consisted of 30 items. The results indicated that, overall, the sample of students with hearing impairments had a generally low level of health beliefs, and that the research sample exhibited the same level of health beliefs regardless of gender. Conclusions:Students with hearing impairments suffer from weakness or inadequacy in their health beliefs. Students with hearing impairments have the same level of health beliefs regardless of gender, indicating no significant gender-based differences in health beliefs. Recommendations:The researchers recommend that teachers in institutions for the hearing impaired allocate part of the first class period to present video clips or educational cards to raise students’ awareness and develop their health beliefs in ways that support their awareness and enhance their daily practices. Suggestions:Conduct a comparative study on health beliefs between students with hearing impairments and their typically developing peers.